2015
DOI: 10.1590/1413-81232015203.10932014
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac misconceptions among healthy adults: implications for the promotion of health in the community

Abstract: cardiac misconceptions among healthy adults: implications for the promotion of health in the communityCrenças erróneas sobre as doenças cardíacas em adultos saudáveis: implicações para a promoção da saúde na comunidade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As for patients with myocardial infarction, a common misconception is that they must avoid stress and excitement in their daily lives [ 6 ]. In a community sample of healthy adults, people who were older, male, or had not attained an academic degree were found to have more misconceptions [ 10 ]. A study conducted among the Amish found that they valued good health, which they believe is a gift from God.…”
Section: Introductionmentioning
confidence: 99%
“…As for patients with myocardial infarction, a common misconception is that they must avoid stress and excitement in their daily lives [ 6 ]. In a community sample of healthy adults, people who were older, male, or had not attained an academic degree were found to have more misconceptions [ 10 ]. A study conducted among the Amish found that they valued good health, which they believe is a gift from God.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship deserves further investigation in order to understand its possible contribution to elicit misconceptions about CHD which are likely to be shared in the community. Therefore, the increasing investment in CHD prevention may prove ineffective if cardiac misconceptions related to risk are not targeted in order to promote realistic risk perceptions of CHD within society (Figueiras et al, 2015). In that sense, the present findings make an important contribution to understanding how individuals judge the risks attached to CHD, and how personal characteristics of different groups of the general population should be taken into account when planning health promotion campaigns in order to promote healthier lifestyles and to reduce the incidence of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an extensive body of research on risk perception, there is a need to have more information concerning which variables influence risk judgements, and the extent to which they may be linked to individual characteristics such as demographic variables, as people make judgements about risk which tend to be consistent with their individual illness beliefs (Gholizadeh et al, 2010). Furthermore, these judgements are likely to be shared and reinforced in the community, raising erroneous beliefs which may have implications for preventive behaviours (Figueiras et al, 2015).…”
Section: Introductionmentioning
confidence: 99%